TRADISI DAN KEARIFAN LOKAL MATAH MARE MASYARAKAT NELAYAN PADA MUSIM KEMARAU DI DESA PASAR LAMA KECAMATAN KAUR SELATAN KABUPATEN KAUR - Saputra, Novryan; Ledyawati (JURNAL ILMIAH IDEA, 2024)
This research aims to explore and analyze the traditions and local wisdom of Matah Mare in Pasar Lama Village, South Kaur District, Kaur Regency, using qualitative research methods supported by data collection techniques through observation, interviews and documentation, and analyzed using the Robert K. Theory method. Merton Functional. The results of the research show that there is a community role in the Matah Mare tradition carried out in Pasar Lama Village by the Serawai tribe in South Kaur District, Kaur Regency, Bengkulu Province. This tradition involves opening floodgates and directing their flow to the sea. The aim of the Matah Mare tradition is to alleviate poverty during the lean season, because the river mouth has lots of fish. The Matah Mare tradition embodies social values ​​including mutual cooperation, sharing wealth with others, harmony, respect for others, and responsibility. The function of the Matah Mare tradition in Pasar Lama Village, South Kaur District, Kaur Regency is as follows: social values ​​such as mutual cooperation, sharing with others, harmony, respect for others, and responsibility. Apart from that, to analyze the manifest and latent functions, the manifest functions include directing water to estuaries to prevent flooding in the rainy season, mutual cooperation, and opening water flows in the lean season to facilitate fish harvesting. Its latent functions include forgotten traditions, coastal erosion, and changes in estuary conditions